2007
DOI: 10.1111/j.1742-1241.2006.01251.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in chronic kidney disease: effects of treatment modality, depression, malnutrition and inflammation

Abstract: In the present study, our aim is to investigate the effects of the treatment modality, depression, malnutrition and inflammation on quality of life (QoL) in chronic kidney disease (CKD). Twenty-six patients with CKD on conservative management, 68 patients on haemodialysis (HD), 47 patients on continuous ambulatory peritoneal dialysis (CAPD) and 66 healthy controls were enrolled in the study. QoL was measured by means of the Short Form-36 (SF-36) and subscale scores were calculated. All patients were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
83
3
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 28 publications
13
83
3
4
Order By: Relevance
“…19 In so me ot her stu di es QOL sco res we re higher in the CAPD pa ti ents. [20][21][22][23][24] The study of Ka lender et al whe re SF-36 was used to eva lu a te QOL of chro nic kid ney di se a se pa ti ents re por ted that the SF-36 sco res we re hig her in the CAPD gro up than HD gro up. 20 Shrest ha et al sta ted that pa ti ents on CAPD ha d bet ter qu a lity of li fe than pa ti ents on HD es pe ci ally in terms of men tal he alth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 In so me ot her stu di es QOL sco res we re higher in the CAPD pa ti ents. [20][21][22][23][24] The study of Ka lender et al whe re SF-36 was used to eva lu a te QOL of chro nic kid ney di se a se pa ti ents re por ted that the SF-36 sco res we re hig her in the CAPD gro up than HD gro up. 20 Shrest ha et al sta ted that pa ti ents on CAPD ha d bet ter qu a lity of li fe than pa ti ents on HD es pe ci ally in terms of men tal he alth.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] The study of Ka lender et al whe re SF-36 was used to eva lu a te QOL of chro nic kid ney di se a se pa ti ents re por ted that the SF-36 sco res we re hig her in the CAPD gro up than HD gro up. 20 Shrest ha et al sta ted that pa ti ents on CAPD ha d bet ter qu a lity of li fe than pa ti ents on HD es pe ci ally in terms of men tal he alth. 21 Gi ni e riCoc co sis et al al so sta ted in the ir study that pa tients on HD tre at ment, par ti cu larly tho se with many ye ars of tre at ment, we re ex pe ri en cing a more com pro mi sed QOL in com pa ri son to CAPD/PD pa ti ents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…또한 우울 (Kalender, Ozdemir, Dervisoglu, & Ozdemir, 2007), 불안 (Tong et al, 2009), 피로 (Rodrigue et al, 2011), 수면 장애 (Cohen, Patel, Khetpal, Peterson, & Kimmel, 2007)와 같은 생행동적 요인이 삶의 질에 부정적인 영향 을 미치는 것으로 보고되었으며 (Wood, Klebba, & Miller, 2000), 사회 적 지지 또한 만성 신부전 환자의 삶의 질에 직접적 (Cohen et al) 또 는 간접적으로 영향을 주는 것으로 보고되었다 (Hoth, Christensen, Ehlers, Raichle, & Lawto, 2007). 영양학적, 신체적 요인은 수면장애 (Cohen et al), 우울 (Kohatsu, 2005) …”
Section: 투석 전 만성 신부전 환자의 삶의 질에 영향을 주는 요인으로 영unclassified
“…Obviously other factors must have contributed to these findings. Kalander et al (2007) reported that the different of QoL based on dialysis modality could be explained by differences in socio-demographic characteristic, patients' clinical features or the methods used to measure the QoL. Hence none of the findings reported to date could be generalised to ESRD patients in other societies or geographic locations.…”
Section: Introductionmentioning
confidence: 98%